The systematic position of Rhytidocaulon (Apocynaceae-Asclepiadoideae) - Bruyns, P. V. (Edinburgh Journal of Botany, 1999)
Rhytidocaulon P.R.O. Bally is reviewed. The relationships with other genera are discussed in the light of the character assessment carried out and it is suggested that it is closest to Caralluma R. Br. subg. Caralluma and Echidnopsis Hook. f. Descriptions of the genus and the eight known species are provided.
Keywords: Arabia; north-east Africa; stapeliads; taxonomy